Foam sclerotherapy – An update - Kobus, S.; Reich-Schupke, S.; Altmeyer, P.; Stücker, M. (Phlebologie, 2010)
Foam sclerotherapy is an efficient and safe technique for the treatment of chronic venous insufficiency. In Germany, the multiplicity of sclerosing agents of past decades has reduced to the agent Aethoxysklerol® (active ingredient: polidocanol). It has been shown that sclerosants are more efficient when administered as foam rather than in liquid form. Only for spider veins are liquid sclerosants equally, or more effective than their foam counterparts. Various techniques can be used to mix the sclerosant with a gas (generally normal room air, alternative: CO2) to produce a foam. The foam's advantage over the liquid form is that it completely displaces the blood from the venous segment to be treated and thereby considerably prolongs the contact time with the vein wall. The various sclerosants lead to marked damage of the vascular endothelium and possibly, the entire venous wall. If sclerotherapy is successful, the vein is ultimately converted into a thread of connective tissue. A sufficient volume of foam is crucial to the success of sclerotherapy of trunk varices, in order to ensure adequate filling of the vessel lumen. Foam sclerotherapy reaches its limit with varicosities of more than 8 mm in diameter, because the rate of thrombosis rises sharply with foam volumes above 10 ml. Foam sclerotherapy may also be used to treat angiodysplasias, vulvar, pudendal and periulcerous varicosities and is quite often the only therapeutic option. The main complications of sclerotherapy are pain in the region of sclerothrombi, haematoma, phlebitis, induration, pigmentation and a metallic taste. Other acute complications are vasovagal reactions, paraesthesias and nausea. Anaphylactic reactions, intra-arterial injections with the possible sequelae, migraine attacks with visual disturbances (scintillating scotoma) and transient neurological deficits have indeed been reported in individual cases, but are very rare.Consideration of the current literature shows that foam sclerotherapy is a safe and quite simple technique for all forms of varicosis. Based on the data now available, it can be stated that foam sclerotherapy is far more effective than liquid sclerotherapy.
Keywords: Sclerotherapy; foam; varicosis